Formulating a fully converged biorefining chain with zero wastewater generation by recycling stillage liquid to dry acid pretreatment operation. (December 2020) - Zheng, Lixiang; Han, Xushen; Han, Tao; Liu, Gang; Bao, Jie
Graphical abstract: Highlights: Direct recycling of wastewater led to a high but gradually reduced ethanol titer. Wastewater recycling by evaporation stabilized cellulosic ethanol production. Combustion of lignin residue satisfied the energy requirement of evaporation. Closed circulation of cellulosic ethanol wastewater was realized. Abstract: Huge wastewater generation is the major challenge of biorefinery technology for production of cellulosic ethanol. This study designed and verified a method for completely recycling of wastewater stream (the stillage liquid from the beer column) in cellulosic ethanol production by dry biorefining processing. When the stillage liquid was directly recycled to dry acid pretreatment operation, ethanol production gradually reduced after two recycles primarily because the inorganic compounds accumulated by around 139%. To ultimately solve this technical barrier, the stillage liquid was evaporated and condensed into distillated water, then recycled to the pretreatment for complete dry biorefining process. This strategy supported a stable cellulosic ethanol production, and the overall mass and heat balance confirmed that only 65% of the lignin residue consumption was used for wastewater evaporation with 35% surplus for electricity generation. This study provided a fully converged biorefining process with a closed-loop wastewater recycling.